2010
DOI: 10.1100/tsw.2010.128
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Virgin Olive Oil Reduces Blood Brain Barrier Permeability, Brain Edema, and Brain Injury in Rats Subjected to Ischemia-Reperfusion

Abstract: Recent studies suggest that dietary virgin olive oil (VOO) reduces hypoxia-reoxygenation injury in rat brain slices. We sought to extend these observations in an in vivo study of rat cerebral ischemia-reperfusion injury. Four groups, each consisting of 18 Wistar rats, were studied. One group (control) received saline, while three treatment groups received oral VOO (0.25, 0.5, and 0.75 mL/kg/day, respectively). After 30 days, blood lipid profiles were determined, before a 60-min period of middle cerebral artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Antioxidant compounds such as polyphenols which are found in some foods have been shown to reduce ischemic damage in animal models [29]. Thyme tea has been shown to improve symptoms of neurological disorder and its use is recommended to all people with neurological disorders [30].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant compounds such as polyphenols which are found in some foods have been shown to reduce ischemic damage in animal models [29]. Thyme tea has been shown to improve symptoms of neurological disorder and its use is recommended to all people with neurological disorders [30].…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of the BBB has been shown in a number of disorders (see the previously referred to reports by Carvey et al, Freeman and Granholm at ASNTR [5, 64] and Mohagheghi et al, Thal in TheScientificWorldJournal [67, 135]. Thal proposes that altered drainage of extracellular fluid due to impairments in the BBB competes with perivascular drainage and could result in the accumulation of A β and other proteins within the brain).…”
Section: Other Neurological Disordersmentioning
confidence: 99%
“…17 Also a study documented that oral administration of olive oil ( physiologic doses of 0.5 and 0.75 ml/kg per day) is cerebroprotective in a rat model of ischemia reperfusion by reduction of brain edema, while the lower dose (0.25 ml/kg per day) was without effect. 16 Recently, we demonstrated that oleuropein treatment ( physiologic doses of 20 mg/kg immediately and 1 hour after spinal cord injury) significantly attenuated expression of tumor necrosis factor alpha (TNF-α) and IL-1β, the potent pro-inflammatory cytokines, and consequently expression of iNOS and COX-2. 77 We also found that oleuropein treatment significantly attenuated expression of poly-(ADP-ribose) polymerase (PARP) and nitrotyrosine, 77 and reduced MPO activity, 78 which is indicating a reduction of the neutrophil influx in the injured spinal tissue.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…13 A further study showed that pretreatment with virgin olive oil for 30 days and 2 h before middle cerebral artery occlusion ( physiologic doses of 0.5 and 0.75 ml/kg per day) resulted in a reduction of infarct volume, while the lower dose (0.25 ml/kg per day) had no effect. 16 Also a study documented that injection of physiologic dose of tyrosol (30 mg/kg) reduced infarct volume on transient focal cerebral ischemia in rats. 15 Other studies have shown that lactate dehydrogenase efflux, as a marker of brain cell death, inhibited in a concentration-dependent manner after 7 days of oral treatment with hydroxytyrosol and hydroxytyrosol acetate ( physiologic doses of 5 or 10 mg/kg per day), 14 and after virgin olive oil intake 12 in rat brain slices subjected to hypoxia-reoxygenation.…”
Section: Anti-apoptotic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation